1994
DOI: 10.1083/jcb.126.4.827
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin condensation during apoptosis is accompanied by degradation of lamin A+B, without enhanced activation of cdc2 kinase.

Abstract: Abstract. Chromatin condensation paralleled by DNA fragmentation is one of the most important criteria which are used to identify apoptotic cells. However, comparable changes are also observed in interphase nuclei which have been treated with cell extracts from mitotic cells. In this respect it is known that in mitosis, the lamina structure is broken down as a result of lamin solubilization and it is possible that a similar process is happening in apoptotic cells. The experiments described in this study have u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
164
0
3

Year Published

1995
1995
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(174 citation statements)
references
References 36 publications
7
164
0
3
Order By: Relevance
“…Chromatin condensation and nuclear disintegration are typical signs of apoptotic cell death. MM.1S cells treated with ABT-737 (2 mM) for 48 h show a marked increase in nuclear condensation, as indicated (Oberhammer et al, 1994).…”
mentioning
confidence: 68%
“…Chromatin condensation and nuclear disintegration are typical signs of apoptotic cell death. MM.1S cells treated with ABT-737 (2 mM) for 48 h show a marked increase in nuclear condensation, as indicated (Oberhammer et al, 1994).…”
mentioning
confidence: 68%
“…34 There have been a number of reports in the literature suggesting that initiation of apoptotic DNA cleavage occurs at matrix attachment regions. 6,7,[35][36][37] The first supporting evidence came from studies that establish that high molecular weight DNA fragments of 50 and 300 kb, produced in early stages of apoptosis, represent structural domains of chromatin, loops and rosettes, respectively. 1,7 It was then suggested that topoisomerase II, located at matrix attachment sites, is responsible for this cleavage since inhibition of its activity generated the same pattern of DNA fragments.…”
Section: Discussionmentioning
confidence: 99%
“…After maturation of the beta-cell phenotype protein spots containing lamin B1 and C2 were up-regulated. Proteolysis of lamins, the major structural proteins of the nuclear envelope, are observed in cells undergoing apoptosis [52]. The relevance of this in relation to beta-cell sensitivity to IL-1β is not clear.…”
Section: Protein Synthesis Chaperones and Protein Foldingmentioning
confidence: 99%